Gestational Smoking and Hypertension as Predictors of Working Memory Functioning in Childhood Attention-Deficit/Hyperactivity Disorder - Marcelle, Enitan T.; Oliva, Mercedes T.; Hinshaw, Stephen P. (Frontiers in Psychology, 2020)
Attention-Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition affecting between five and eight percent of all children and adolescents, characterized by impairing levels of inattention, hyperactivity, and impulsivity. Existing cognitive models of ADHD have placed working memory (WM) deficits at the core of ADHD and suggest that primary WM deficits may also underlie the additional deficits associated with the condition. Although not all children with ADHD show WM deficits, those with such deficits have been found to have worse functional outcomes when compared to their diagnosed peers with typical WM functioning. Even so, contributors to the variability of impaired WM functioning seen within the population remain unknown. In the present study we examined the association between two known pre- and perinatal risk factors for impaired cognitive functioning--gestational smoking and hypertension—in three independent samples of children and adolescents with ADHD. Contrary to hypotheses and existing literature, presence of high blood pressure during pregnancy was found to be a positive predictor of offspring WM capacity in one of three samples. Implications and considerations for future research are discussed.